2021
DOI: 10.1152/ajpendo.00483.2020
|View full text |Cite
|
Sign up to set email alerts
|

Is nuclear sirtuin SIRT6 a master regulator of immune function?

Abstract: The ability to ward off pathogens with minimal damage to the host determines the immune system's robustness. Multiple factors, including pathogen processing, identification, secretion of mediator and effector molecules, and immune cell proliferation and differentiation into various subsets, constitute the success of mounting an effective immune response. Cellular metabolism controls all of these intricate processes. Cells utilize diverse fuel sources and switch back and forth between different metabolic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 195 publications
0
4
0
Order By: Relevance
“…Although few studies have shown SIRT6 to affect immune cell function through directly regulating immunometabolism, SIRT6 has been found to regulate immune cell activity via effects on PI3K/Akt, NF-κB, and HIF-1α as discussed above. The above three signaling pathways could be involved in regulation of the TCA cycle, glycolysis, pentose phosphate pathway, and Warburg effect, thereby affecting the energy metabolism of immune cells in the resting state and activated state ( 72 , 89 94 ). SIRT6 also regulates intracellular levels of NAD + , which is an electron acceptor with a key role in cell metabolism.…”
Section: Sirt6 and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although few studies have shown SIRT6 to affect immune cell function through directly regulating immunometabolism, SIRT6 has been found to regulate immune cell activity via effects on PI3K/Akt, NF-κB, and HIF-1α as discussed above. The above three signaling pathways could be involved in regulation of the TCA cycle, glycolysis, pentose phosphate pathway, and Warburg effect, thereby affecting the energy metabolism of immune cells in the resting state and activated state ( 72 , 89 94 ). SIRT6 also regulates intracellular levels of NAD + , which is an electron acceptor with a key role in cell metabolism.…”
Section: Sirt6 and Immunitymentioning
confidence: 99%
“…Therefore, SIRT6 is likely to regulate immune cell proliferation, growth, and function by affecting immunometabolism. Pillai’s review discusses this point in detail and proposes that SIRT6 participates in short-term regulation of immune cells through PTMs and long-term regulation through transcriptional regulation of metabolism-related genes ( 89 ). Therefore, how SIRT6 regulates immunometabolism and how this regulation affects cell function will be an interesting research direction.…”
Section: Sirt6 and Immunitymentioning
confidence: 99%
“…SIRT6 is a nuclear SIRT isoform that interacts with chromatin and finely regulates genome maintenance, response to oxidative stress, inflammation, senescence, and metabolism. Constant exposure to oxidative stress has been demonstrated to lead to the onset of a senescence phenotype [ 97 ]. This phenotype consists of a reduction of cell growth and proliferation, along with higher expression of the senescence-associated β-galactosidase.…”
Section: Sirtuins and Diabetic Retinopathymentioning
confidence: 99%
“…High Sirt6 expression levels are observed in the immune system. It may be a possibly a negative regulator of immune cell function and metabolism, which related to neutrophil inactivation and increased the polarization to M2 macrophages ( Pillai and Gupta, 2021 ).…”
Section: Histone Deacetylases In Tumor Immunity Regulationmentioning
confidence: 99%